Theory and practice of procurement flexibility: a model for suppliers and manufacturers - Jeeva, Ananda; Dickie, Carolyn (Curtin University of Technology, 2009)
This paper is designed to extend knowledge of flexibility in manufacturing supply chains through examination of procurement entity relationships, flexibility classifications and their commonalities as used by practitioners. Data were collected from procurement, supply chain, logistics and manufacturing managers in Australian companies in 17 Standard Industry Classification categories. The research findings suggest that Australian manufacturing organisations have not sufficiently integrated their manufacturing strategies with their organisational strategies and, more importantly, suppliers to manufacturers do not have sufficient flexibility in their supply activities. One limitation pertains to the possibility that targeted respondents may not have the assumed intimate knowledge of their organisation's procurement activities, or are biased regarding their view of the quality of the organisation's procurement performance. The major contributions of the study are the development of a definition of procurement flexibility (ProcFlex), a conceptual model for use as a benchmarking tool to measure procurement flexibility, and the presentation of an integrated model of ProcFlex for use by manufacturers and their suppliers to be moreresponsive and increase competitive advantage.